2019
DOI: 10.7150/thno.30716
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes from M1-Polarized Macrophages Enhance Paclitaxel Antitumor Activity by Activating Macrophages-Mediated Inflammation

Abstract: Objective: Exosomes (Exos) are membrane-encased vesicles derived by nearly all cell types for intercellular communication and regulation. They also received attention for their use as natural therapeutic platforms and drug delivery system. Classically activated M1 macrophages suppress tumor growth by releasing pro-inflammatory factors. This study investigated the suitability of M1-exosomes (M1-Exos) as drug carrier and their effect on the NF-κB signal pathway and further detected whether macrophages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
218
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 332 publications
(226 citation statements)
references
References 70 publications
8
218
0
Order By: Relevance
“…106,107 Recently, studies using exosomal delivery of PTX to address this deficiency have been widely reported. For example, Wang et al 108 selected classical activated M1-type macrophage-derived exosomes as a carrier to reduce the toxicity of PTX and improve its bioavailability. Not only has PTX been successfully delivered to tumor tissue of mice, but also by activating NF-κB pathway it establishes a pro-inflammatory environment to enhance the therapeutic effect of PTX.…”
Section: Type Of Drug Loadingmentioning
confidence: 99%
“…106,107 Recently, studies using exosomal delivery of PTX to address this deficiency have been widely reported. For example, Wang et al 108 selected classical activated M1-type macrophage-derived exosomes as a carrier to reduce the toxicity of PTX and improve its bioavailability. Not only has PTX been successfully delivered to tumor tissue of mice, but also by activating NF-κB pathway it establishes a pro-inflammatory environment to enhance the therapeutic effect of PTX.…”
Section: Type Of Drug Loadingmentioning
confidence: 99%
“…Western blotting was performed according to previous studies [20]. The obtained PVDF membrane was incubated overnight with primary antibodies against BMP-2 (1:1000), RUNX2 (1:1000), Smad1 (1:1000), HIF-1α (1: 1000), OPN (1:1000), OGN (1:1000) (Cell Signaling Technology, MA, USA) and VEGFA (1:1000) (Abcam, Cambridge, UK) at 4°C.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…While tumor-associated macrophages have been shown to promote tumor progression, angiogenesis, immunosuppression and metastasis, a study by Cheng et al describes that their EVs actually promote inflammation-related responses, which can enhance immunotherapy effects against cancer cells [88]. Moreover, other studies suggest that by using EVs from macrophages polarized towards an M1-like phenotype (which has antitumoral features), it is possible to decrease the proliferation of malignant cells, enhance immune responses and increase the effectiveness of drugs [89].…”
Section: Antitumoral Effectsmentioning
confidence: 99%